IMPLEMENTASI ECO-EDUCATION DI SEKOLAH PERKOTAAN MELALUI BUDIDAYA VERTIKULTUR TANAMAN HORTIKULTURA ORGANIK - Budiwati, Siti Mariyam, Tutiek Rahayu (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2014)
The purpose of this activity were: (1) Providing instructional mediawith eco-education minded at the urban school with limited land area; (2)Providing knowledge about the benefits of a healthy environment and organicfoods; (3) Providing verticultural farming of organic horticultural plantskills to students.This service activities conducted with visiting the location, namelyin SMP Muhammadiyah 5 Patehan Lor Road Yogyakarta. The target activitywere 5 teachers and 25 students, the activities initiated by the pretestand ending with posttest. The activities included: (1) presenting the materialof a healthy environment and healthy food, nutritious and environmentallyfriendly; (2) demonstrating and practicing of verticultural farming of organichorticultural plants; (3) evaluating the effectiveness of action after onemonth activities.The evaluation was carried out by reviewing the one month activitiesto see success of practiced verticultural cultivation. Then, given a questionnairesheet about the activities benefits, and knowing the activities advantagesand disadvantages. This service activities could be said to be successfulbecause all participants were practicing the verticultural farming of organichorticultural plants in a groups.Keywords: eco-education, verticultural cultivation, and organic horticulturalplants